2023
DOI: 10.1039/d2fo02628g
|View full text |Cite
|
Sign up to set email alerts
|

Dose–response meta-analysis of ultra-processed food with the risk of cardiovascular events and all-cause mortality: evidence from prospective cohort studies

Abstract: Background: Previous meta-analyses included abundant cross-sectional studies, and/or only assessed high versus low categories in UPF consumption. We conducted this meta-analysis based on prospective cohort studies to estimate the dose–response...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 48 publications
0
38
0
1
Order By: Relevance
“…Additionally, we found evidence of excess significance bias in nine (32%) of the 28 pooled analyses with three or more original research articles listed in supplementary table G. This bias was evident in associations between higher ultra-processed food exposure and all cause mortality (dose-response and non-dose-response),43 hypertension,44 abdominal obesity,42 metabolic syndrome,45 non-alcoholic fatty liver disease,46 obesity (dose-response and non-dose-response),42 and type 2 diabetes 47. Small study effects were evident in five (18%) of the 28 pooled analyses with three or more original research articles, as indicated in supplementary table G. We observed these effects in associations between higher ultra-processed food exposure and all cause mortality (dose-response and non-dose-response),43 breast cancer,40 metabolic syndrome,45 and obesity (dose-response) 42…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…Additionally, we found evidence of excess significance bias in nine (32%) of the 28 pooled analyses with three or more original research articles listed in supplementary table G. This bias was evident in associations between higher ultra-processed food exposure and all cause mortality (dose-response and non-dose-response),43 hypertension,44 abdominal obesity,42 metabolic syndrome,45 non-alcoholic fatty liver disease,46 obesity (dose-response and non-dose-response),42 and type 2 diabetes 47. Small study effects were evident in five (18%) of the 28 pooled analyses with three or more original research articles, as indicated in supplementary table G. We observed these effects in associations between higher ultra-processed food exposure and all cause mortality (dose-response and non-dose-response),43 breast cancer,40 metabolic syndrome,45 and obesity (dose-response) 42…”
Section: Resultsmentioning
confidence: 80%
“…The systematic search identified 430 de-duplicated articles (fig 1). After applying the eligibility criteria, we included 14 meta-analysis studies with 45 distinct pooled analyses 1718404142434445464748495051…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The systematic search identified 430 deduplicated articles (Figure 1). After applying the eligibility criteria, 14 meta-analysis studies with 45 distinct pooled analyses were included 18,[41][42][43][44][45][46][47][48][49][50][51][52][53] .…”
Section: Resultsmentioning
confidence: 99%